Investigating The Obstacles That Face Primary and Intermediate Students in Using Mobile Assisted Language Learning (MALL) from Teachers' Perspectives (Journal of the College of Basic Education, 2020)
The aim of the study is to investigate the obstacles that face the primary and intermediate students in utilizing the mobile applications in learning English language from the teachers' perspectives. The participants of the study were male and female teachers from the primary and intermediate schools in the first Al-Rusafa Education directorate, first Al-Karkh Education directorate, and Heet Education directorate in Anbar. To achieve the aim of the study, the following question was set: “what do the teachers' perceive as obstacles to utilize MALL for English learning?" A questionnaire was used to answer the question of the study. The findings revealed that the teachers agreed on some obstacles that face the students to use MALL in learning English language. The highest percentage as an obstacle that face students was entitled" The compatibility between the material in the textbook and the mobile applications learning program" followed the item entitled "Lack and absence of teachers' training sessions on using MALL".